Transforming Language Learning and Reading Engagement with Metacognitive-Based Trilingual Smartcards - Sari, Ni Ketut Novita; Bayu, Gede Wira (Journal of Education Technology, 2024)
This study started from the problem of low language skills and reading engagement of elementary school students. This study aims to test the effectiveness of developing e-booklet-based trilingual smartcards media in metacognitive learning to improve students' language skills and reading engagement. This study uses the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model as a systematic approach. Data were collected through interviews with teachers and questionnaires to students, while the validity, practicality, and effectiveness of the media were analyzed through statistical tests. The results showed that e-booklet-based trilingual smartcards media has a high level of validity based on expert evaluations of material, media, and instructional design. In addition, student responses showed that this media is very practical to use in learning. Effectiveness testing with statistical analysis showed a significant increase in students' language skills and reading engagement with a significance value of p <0.001 (criterion Sig. <0.05). These results indicate that the developed media can be an innovative alternative in improving the quality of language learning. The implications of this study indicate that the integration of e-booklet-based trilingual smartcards in metacognitive learning can optimize students' literacy strategies and increase their engagement in reading activities.